KEBIJAKAN MADRASAH DALAM MENINGKATKAN MUTU PENDIDIKAN MELALUI PROGRAM UNGGULAN UNTUK MENCAPAI SUSTAINABLE DEVELOPMENT GOALS (SDGs) DI MAN KABUPATEN LOMBOK TIMUR - Triya Rezeki Umais; Muhammad Makki; Fahruddin Fahruddin; Sudirman Wilian; Mohammad Mustari (Jurnal Manajemen Pendidikan, 2026)
This study aims to examine madrasah policies for improving the quality of education implemented through flagship programs to achieve Sustainable Development Goal (SDG) 4: Quality Education. This is a qualitative study using a multiple-case study approach conducted at two research sites in East Lombok Regency. The subjects of this study include madrasah principals, vice principals, committees, advisors, and students. Data collection techniques included observation, interviews, and documentation. Data analysis utilized the Miles and Huberman model, comprising data reduction, data presentation, and drawing conclusions. The results of this study indicate that the flagship program policies at both madrasahs are based on an analysis of the needs and characteristics of the madrasahs using different approaches. MAN IC Lombok Timur tends to adopt a top-down approach focused on academic excellence, while MAN 1 Lombok Timur employs a bottom-up approach by offering extracurricular activities capable of accommodating all potential interests and talents. The implementation of flagship programs at both madrasahs contributes to quality improvement, competency development, and graduate competitiveness in line with SDG 4 indicators. The impact of flagship program policies extends beyond student achievement to include educational quality, attractiveness, and the madrasah’s reputation within the community.